Self-Compassion dan Hope pada Guru Sekolah Inklusi - Isyah Rodhiyah; Pratiwi Widyasari (Psympathic : Jurnal Ilmiah Psikologi, 2021)
This study aims to examine the correlation between self-compassion and hope on teachers in inclusive schools. This study used quantitative method with cross-sectional design with correlational research type. The participants were 162 inclusive primary school teachers in Jakarta, Depok, and Bogor, who were recruited through nonprobability sampling technique that is convenience sampling. The adapted Adult Hope Scale (AHS) and Self-Compassion Scale (SCS) were used as instrument in this study. The findings show that there is a significant positive correlation between self-compassion and hope. This relationship can be caused by mental support, self-confidence, positive attitude, and the increase of competency perception based on self-compassion that may facilitate the individuals to have better hope.